2015
DOI: 10.1007/s00296-015-3314-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-α therapy reduces endothelial cell activation in non-diabetic ankylosing spondylitis patients

Abstract: Endothelial dysfunction can be detected by the presence of elevated levels of biomarkers of endothelial cell activation. In this study, we aimed to establish whether correlations of these biomarkers with characteristics of patients with ankylosing spondylitis (AS) exist. We also studied the effect of anti-TNF-α therapy on these biomarkers. Serum sE-selectin, MCP-1 and sVCAM-1 levels were measured by ELISA in 30 non-diabetic AS patients undergoing anti-TNF-α therapy, immediately before and after an infusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The chronic production of C reactive protein (CRP) and inflammatory cytokines such as tumour necrosis factor α and IL-6 may result in a hypercoagulable state 45. Additionally, some studies of patients with AS have demonstrated elevations in E-selectin, MCP-1 and (soluble vascular adhesion molecula-1 (sVCAM-1)46 suggesting possible endothelial dysfunction. Furthermore, there have been some conflicting data with regard to impaired endothelial function as measured by flow-mediated vasodilation, common carotid intima–media thickness and aortic pulse-wave velocity45 in patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic production of C reactive protein (CRP) and inflammatory cytokines such as tumour necrosis factor α and IL-6 may result in a hypercoagulable state 45. Additionally, some studies of patients with AS have demonstrated elevations in E-selectin, MCP-1 and (soluble vascular adhesion molecula-1 (sVCAM-1)46 suggesting possible endothelial dysfunction. Furthermore, there have been some conflicting data with regard to impaired endothelial function as measured by flow-mediated vasodilation, common carotid intima–media thickness and aortic pulse-wave velocity45 in patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cardiovascular risk in AS patients and the fact that endothelial dysfunction is reversible after a reduction in atherosclerotic risk factor by life-style modifications and pharmacological treatment [44] provide a strong rationale for early therapeutic intervention. A beneficial effect of infliximab on endothelial dysfunction in non-diabetic AS patients, manifested by a reduction in level of biomarkers of endothelial cell activation such as soluble E-selectin and soluble VCAM-1, was observed by Genre et al [45]. Also, Syngle et al [46] found that infliximab improves both endothelial dysfunction measured by FMD and inflammatory AS activity in previously anti-TNF-naive patients.…”
Section: The Effect Of Drugsmentioning
confidence: 92%
“…111 Interestingly, it has also been shown that just after infliximab infusion, adhesion molecules used as surrogate markers for endothelial activation like sE-selectin, are significantly reduced in AS non-diabetic patients. 112 Treatment with TNFi has also beneficial effects in microvascular function, since endothelium-dependent vasodilation and capillary recruitment was found to be improved in a small cohort of AS patients treated with etanercept for 1 month. 113 Atherosclerotic lesions seem to be significantly improved in SpA patients treated with TNFi.…”
Section: Surrogate Markersmentioning
confidence: 99%